The Development Of Indonesian Islamic Civilization In The Pre-Independence Periode - Millatul Aliyah, Septiana; Nazilah, Jihan (Sekolah Tinggi Agama Islam (STAI) Ibnu Rusyd Kotabumi, 2023)
This study aims to analyze the development of Islamic civilization in Indonesia during the pre-independence period. By using the library research method (library research), the data obtained from the results of books and journals. This research shows that; 1) Socio-cultural conditions in the pre-Indonesian era underwent many changes for the better. 2) Government system. In 1755, with Giyanti's approval, the VOC succeeded in becoming the holder of political power on the island of Java. 3) Da'wah strategy through dialogue between traders and buyers, by teaching education at Islamic boarding schools. 4) The challenges of the scholars in conveying the teachings of Islam were not only from the colonizers, but from the scholars and the Muslims themselves. 5) Figures who were influential in the development of Islamic civilization in Indonesia before independence, including Hamzah Fauzi, Sheikh Muhammad Yusup Al-Makasari, the Walisongo etc. This study is important to add to sources of study of Islamic history in Indonesia, especially the scarcity of themes regarding the development of Islamic civilization in Indonesia during the pre-independence period.